2019
DOI: 10.3389/fpls.2019.00188
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Approach Reveals Differences in Host Plant Chemistry Before and After Infestation With Different Pea Aphid Host Races

Abstract: The pea aphid ( Acyrthosiphon pisum ), a phloem-sucking insect, has undergone a rapid radiation together with the domestication and anthropogenic range expansion of several of its legume host plants. This insect species is a complex of at least 15 genetically different host races that can all develop on the universal host plant Vicia faba . However, each host race is specialized on a particular plant species, such as Medicago sativa , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 96 publications
1
40
0
1
Order By: Relevance
“…The two A. pisum host plants used in this study are known to vary significantly in essential amino acid profiles (35) and metabolite profiles, including host plant defense compounds (38, 39). Aphid stylectomy experiments have also shown that fava bean and alfalfa have different concentrations of arginine, isoleucine, leucine, lysine, phenylalanine, tryptophan, tyrosine, valine, and histidine, with alfalfa generally having lower concentrations of essential amino acids than fava bean (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two A. pisum host plants used in this study are known to vary significantly in essential amino acid profiles (35) and metabolite profiles, including host plant defense compounds (38, 39). Aphid stylectomy experiments have also shown that fava bean and alfalfa have different concentrations of arginine, isoleucine, leucine, lysine, phenylalanine, tryptophan, tyrosine, valine, and histidine, with alfalfa generally having lower concentrations of essential amino acids than fava bean (35).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the metabolite profiles among the A. pisum host plants alfalfa, fava bean, pea, and red clover, Sanchez-Arcos et al (38) found that alfalfa plants contain the highest number of unique metabolites, especially compared to that of fava bean plants. Notably, Sanchez-Arcos et al (38) found that saponins, a known A.…”
Section: Discussionmentioning
confidence: 99%
“…Several omics strategies alone or in combination have been used to evaluate plant-aphid, and plant-insect interactions [for example: ( Wu and Baldwin, 2010 ; Maag et al., 2015b ; Tzin et al., 2015 ; Zhou et al., 2015 ; Wozniak et al., 2017 ; Kiani and Szczepaniec, 2018 ; Erb and Reymond, 2019 ; Nalam et al., 2019 ; Sanchez-Arcos et al., 2019 ; He et al., 2020 ; Zhang et al., 2020 ; Zogli et al., 2020 )]. In general, these studies have shown extensive changes in the transcriptomes and metabolomes upon insect herbivory.…”
Section: Introductionmentioning
confidence: 99%
“…The net result of these changes in TF expression levels is the modulation of primary and secondary metabolic pathways, which serve to trigger defense responses to mitigate herbivory. Although several components of defense responses are conserved among multiple plant species, plant genotype, environment, and other factors can lead to variations in the cellular metabolism of the same hosts challenged by insect herbivores ( Coppola et al., 2013 ; Maag et al., 2015a ; Castano-Duque and Luthe, 2018 ; Muneer et al., 2018 ; Sanchez-Arcos et al., 2019 ; Zhao et al., 2019 ). Despite variations in metabolite profiles, certain pathways and compounds produced by these pathways are known to confer protection to plants against biotic stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Annotation and characterisation of unknown molecular or chemical features is the bottleneck of untargeted metabolomics studies which limits the discovery of relevant biological markers to a reduced number of overrepresented chemical classes. Phenylpropanoids constitute one of these examples of a recurrent marker of multiple agronomic trait or biological activities with emphasis on chlorogenic acid and flavonoids [35][36][37][38][39][40]. The large-scale nature of untargeted metabolomics studies requires high throughput methods that likely favour the extraction and detection of, for example, phenylpropanoids and underestimate the presence of minor chemical families are likely to be a contributing factor to these outcomes.…”
Section: Plos Onementioning
confidence: 99%